Covid-19 Pandemic: The fine line between mental health and the health-disease process in nursing undergraduates (Research, Society and Development, 2022)
Social isolation due to the COVID-19 pandemic is considered one of the factors with the greatest impact on the mental health of Brazilians, especially on the health of academics. These impacts may be related to the various anxiety and depression events developed by these students during their period of social distancing. The present study is an integrative review, defined as one that condenses previous research, bringing global conclusions from a specific body of literature, which allows the construction of a broad analysis and contributes to discussions on research methods and results. To this end, a critical analysis of the selected articles was carried out, exposing the results found through a table, thus characterizing a qualitative approach. Then, the results were discussed based on the comparison of the main findings between the authors, confronting the different evidences about the mental health of nursing students during the COVID-19 pandemic. It is concluded that the greatest impact for students of traditional nursing education were the remote classes, since some subjects worried the students about the practical classes, being nursing a science that works with the experience of the environment, motor practices, and contact visual. Therefore, consultations with psychologists and psychiatrists free of charge in online service programs are necessary, and this project may be promoted by the public authorities or even by the higher education institution to which the academic is enrolled, so that it is possible to mitigate the feelings that are felt by nursing students in this pandemic period.